Transformasi Digital dalam Manajemen Keuangan UMKM untuk Meningkatkan Daya Saing - Muhammad Roy Aziz Haryana; Betanika Nila Nirbita; Syahida Norviana; Lu'lu'ul Jannah; Willa Putri Malinda Buchori (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
In reality, there are still MSMEs that are hampered and lack understanding in preparing financial reports, both manually and using the provided applications. The purpose of this community service is to increase MSMEs' understanding of the importance of good and correct financial management, train MSMEs in basic accounting records and preparing financial reports according to SAK EMKM, introduce and train the use of digital financial applications to increase efficiency and transparency, and encourage the adoption of digital technology in MSME financial operations to increase competitiveness. The methods used in this service are providing counseling, education, training (tutorials and exercises), and evaluating activities using questionnaires. Based on the implementation of the community service activities that have been carried out, the conclusion obtained is that in general, this activity has succeeded in having a positive impact, both for participants and for partners (MSMEs), in an effort to realize MSMEs that are more independent and financially prosperous. This activity also supports programs at the Gunungkidul Department of Industry, Cooperatives, SMEs, and Manpower. In addition, the government will also implement a follow-up program with village funds to provide intensive training and mentoring to business actors (MSMEs).